Tinjauan Viktimologis Eksploitasi Seksual Terhadap Anak: Studi Kasus Putusan Nomor 253/Pid.Sus/2023/PN Gto - Ainun Kusuma Dewi, Ainun (Law Research Review Quarterly, 2025)
Child sexual exploitation is a serious and complex problem that occurs globally, with profound physical, psychological, and social impacts on victims. This study analyzes cases of child sexual exploitation through the perspective of victimology, which highlights the vulnerability of victims and the mechanisms of victimization. The research method used is the juridical normative legal method. This study results in that the analyzed cases show how the perpetrators build manipulative relationships and conduct grooming systematically to exploit victims. Comprehensive prevention and prosecution efforts are needed, including preventive approaches in the form of education, improving family welfare, and environmental supervision, as well as repressive approaches through law enforcement and victim rehabilitation. Indonesia has adopted various international instruments and laws that support child protection and the fight against this crime. A victimological approach is essential to understand patterns of exploitation and formulate effective protection strategies to ensure children's rights and welfare.